2018
DOI: 10.1097/shk.0000000000001015
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Thrombocytopenia During Septic Shock: A Multiplex Cluster Analysis of Endogenous Sepsis Mediators

Abstract: Multiple mechanisms seemed involved in thrombocytopenia during septic shock, including endothelial dysfunction/coagulopathy, hemodilution, and altered thrombopoiesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 33 publications
2
39
0
3
Order By: Relevance
“…More importantly, the innate immune responses in Rag2 KO rats, such as high serum levels of TNFa, IL-1, IL-6, and IL-10, and the development of thrombocytopenia also represent those seen in patients with sepsis (22,23). A recent study shows that innate immune response is a factor involved in thrombocytopenia pathogenesis in sepsis patients (24). Thus, this rat sepsis model could provide more insight into mechanism study of sepsis-associated thrombocytopenia.…”
Section: Discussionmentioning
confidence: 89%
“…More importantly, the innate immune responses in Rag2 KO rats, such as high serum levels of TNFa, IL-1, IL-6, and IL-10, and the development of thrombocytopenia also represent those seen in patients with sepsis (22,23). A recent study shows that innate immune response is a factor involved in thrombocytopenia pathogenesis in sepsis patients (24). Thus, this rat sepsis model could provide more insight into mechanism study of sepsis-associated thrombocytopenia.…”
Section: Discussionmentioning
confidence: 89%
“…The platelet count was correlated with thrombopoiesis growth factors, innate immunity/endothelial dysfunction, and platelet activation biomarkers. 22 Moreover, pneumococcus directly promotes platelet activation and aggregation. 4 Therefore, thrombocytopenia is usually thought to reflect infection severity associated with higher mortality, including in CAP patients.…”
Section: Discussionmentioning
confidence: 99%
“…We found that DEX blunted LPS-induced thrombocytopenia, a hallmark of sepsis and endotoxemia [45]. Platelet activation and local coagulation is a protective mechanism against endothelial dysfunction [46], and against pathogens serving their trapping and elimination [47]. However, exaggerated platelet activation is a major contributor to thrombocytopenia and may lead to disseminated intravascular coagulation, and ultimately to multiple organ failure [47].…”
Section: Discussionmentioning
confidence: 99%